Concepts of Justice and National Context Outlining Legal Comparisons Between the Federal Republic of Germany, the United States of America, and the People’s Republic of China - Möllers, Thomas (Potchefstroom Electronic Law Journal, 2022)
Comparative law holds the promise of improving knowledge. Looking at other legal systems enables a nuanced understanding of the rules of one’s own country. While comparative law traditionally starts with a concrete issue, the purpose of this paper is to explore why concepts of justice often differ widely from country to country. The following article compares three major economic powerhouses: the United States, the People’s Republic of China and the Federal Republic of Germany. It will discuss the differences between a liberal and a social market economy, as well as the role of the constitution in society. The outline concludes by looking at the question of when different concepts of justice might converge.